By(wa)ć mentorem czyli o dylematach i pułapkach mentoringu - Piorunek, Magdalena (Wydawnictwo Naukowe UAM, 2016)
Mentoring is regarded as a method of comprehensive development of a protégé’s potential, which required a steady approach, regular contact and collaboration with the mentor. A non-directive interaction between the master and protégé, mentoring is a relation that involves inspiration, stimulation and leadership. At its foundation lies a belief that it is possible to have impact on other individuals in their zones of proximal development (Vygotsky) based on the skill (art) of bringing out protégé’s strong assets (Seligman) within joint involvement episodes (Schaffer). A mentor is expected to motivate and encourage her protégé to be active as well as to develop an honest, open and friendly collaboration environment that is based on mutual respect. As a work and joint involvement method, mentoring is endorsed in education, labour market institutions, learning organisations (Senge). The concept of a mentor is linked to those of a master, authority, important person, example to follow, leader, and to some extent those of a teacher. To what extent this mentor- protégé relation can be formalised? Is it, as claimed by critical pedagogy, a component of pastoral power where the protégé is required to give herself up and surrender her development to the hands of the leader, i.e. a pastor, mentor (Foucault)? Is a teacher (occasionally) a mentor? These selected dilemmas, questions and doubts about the mentoring concept are raised in this text.
(Occasionally) Being a Mentor or Dilemmas and Traps of Mentoring
Keywords: mentoring; mentor; leader; development support; protégé’s own resources; lifelong guidance